(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article covers the assessment of the effectiveness of innovative management of enterprises, as well as its methods. Also, the analysis of methods for assessing the effectiveness of innovative management of industrial enterprises and the grouping of indicators of the effectiveness of innovative management at the enterprise were carried out.